PENGGUNAAN SOFTWARE SIBELIUS SEBAGAI MEDIA PEMBELAJARAN DARING PADA MATA KULIAH HARMONI TONAL DASAR DI DEPARTEMEN PENDIDIKAN MUSIK UPI - Ray Gisella Zakiah, - (2021)
This research is entitled The Use of Sibelius Software in the Basic Tonal Harmony course at the Department of Music Education. Learning is carried out online in the midst of the Covid-19 pandemic situation. The use of learning media is very important in the online learning process during the Covid-19 pandemic situation. Learning media is useful for students' understanding of the material of musical notation and chords. The purpose of this study is to determine the effectiveness of using Sibelius Software in online Basic Tonal Harmony courses. This study uses a descriptive method with a qualitative approach so that the results can be described in detail. The research technique used by the researcher is interviews and literature study. Based on the results of the research, learning is carried out online using the Sibelius Software as a learning medium that is quite maximal and quite effective. The results of using the Sibelius Software in the online Basic Tonal Harmony course that are felt by lecturers and students produce good results in using the Sibelius Software to help and simplify the online learning process. Keywords: Online learning, effectiveness, Sibelius Software